MODEL ANGKA PARTISIPASI SEKOLAH JENJANG SMA SEDERAJAT DI PROVINSI BALI - WIDIADNYANI, NI LUH GEDE; SUCIPTAWATI, NI LUH PUTU; SUSILAWATI, MADE (E-Jurnal Matematika; Vol 8 No 3 (2019), 2019)
Each distritcs in Bali Province has an uneven high school enrollment rate. The lowest of high school enrollment rate is Bangli Regency in 2012 at 41,99 percent and the highest is Klungkung Regency in 2014 at 91,49 percent. The purpose of this work is to modeling and determine the significant factors that affect the high school enrollment rate in Bali Province by applying panel data regression. The results show the suitable model is fixed effect model (FEM) that is fixed individual effect model and significant affect by HDI, the percentage of poverty, and gini ratio.